Comparison of Efficacy of Colchicine Plus Dual Antiplatelet Therapy vs. Dual Antiplatelet Therapy Alone in Patients with Acute Myocardial Infarction Undergoing Primary PCI - Ameen, Muhammad; Nawaz , Ali; Khan , Hafiz waleed; Mehreen , Sobia; Adil, Muhammad; Asad, Muhammad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the impact of colchicine on inflammatory markers, left ventricular function, and major adverse cardiovascular events (MACE) over 3 months.Study Design: Quasi experimental study.Place and Duration of Study: Cardiology Department of Armed Forces Institute of Cardiology, National Institute of Heart Diseases, Rawalpindi Pakistan, from Jun 2025 to Oct 2025.Methodology: Two hundred fifty-nine Acute Myocardial Infarction (AMI) patients undergoing primary percutaneous coronary intervention (PPCI) were enrolled through nonprobability consecutive sampling with non-random allocation into two groups: Experimental-Group 127 received colchicine + Dual Antiplatelet Therapy (DAPT), and Control-Group 132 received DAPT alone. The endpoints were changes in C-reactive protein (CRP) and left ventricular ejection fraction (LVEF) and MACE.Results: Out of 259, mean age was 63.11±10.63 years in the Colchicine-Group and 60.43±11.01 years in the non-Colchicine-Group, with males comprising 90.6% and 84.1% of participants, respectively. Baseline characteristics were similar between groups. No statistically significant differences were found in CRP levels or LVEF at 1 and 3 months. At 3 months, MACE rates—including mortality (0% vs 1.5%), recurrent MI (0% vs 0.8%), heart failure (0.8% vs 0.7%), and stent thrombosis (0.8% vs 0.7%)—showed no significant difference between colchicine and control groups.Conclusion: In AMI patients undergoing primary PCI, adding colchicine to DAPT did not significantly reduce inflammatory markers, improve left ventricular function, or decrease MACE over 3 months. Larger randomized controlled trials with longer follow-up are recommended.